3 CPR by first responders improves acid-base balance and prognosis in out-of-hospital non-traumatic cardiac arrest. (26th April 2019) - Hernández-Tejedor, A; Corral, E; de Elías, R; Suárez, R
Abstract : Background: Early basic-CPR has been shown to be effective. However, its effect on homeostasis in non-traumatic out-of-hospital cardiac arrest (OHCA) is unknown. We analyze pathophysiological and prognostic consequences of basic-CPR performed by first responders (FR) previous to EMS arrival. Method: Prospective observational cohort study including all patients treated for OHCA by an EMS from 2015 to 2017. Basic-CPR by FR and venous blood gas by Epocal (Ottawa, Canada) at the beginning of advanced-CPR were covariates. Dependent variables included analytical values and final outcomes (ROSC and final neurological condition CPC grades I–II). Statistical analysis: Kolmogorov-Smirnov/Lilliefors test of normality, bivariate (T-test and Chi-square-test) and multivariate (logistic regression and recursive partitioning) analysis and association measures (odds ratio-OR). Results: Our EMS attended 749 OHCA. Eighty-seven cases were excluded due to lack of data on gasometry (52)/FR (35). We analyzed 662 cases (137 women, 65.1±16.1 years-old), 46.1% were shockable rhythms and 63% received basic-CPR. pH was 7.13±0.15 in CPR-by-FR-cases and 7.06±0.18 in non-CPR-by-FR-cases (p<0.001). PvCO2 69±23 vs 77±25 mmHg (p<0.001), base excess −6.6±5.4 vs −8.6±6.6 mmol/L (p<0.001) and lactate 6.4±2.9 vs 7.1±3.3 mmol/L (p=0.008). CPR-by-FR (OR 1.83, CI95% 1.30–2.56, p<0.001) and shockable-rhythm (OR 3.32, CI95% 2.37–4.65, p<0.001) were independently associated with higher pH. ROSC occurred in 62.8% of CPR-by-FR-cases and 54.7% of non-CPR-by-FR-cases; OR 1.40, CI95% 1.02–1.93, p=0.039). Recovery CPC I–II occurred in 27.1% of CPR-by-FR-cases and 19.2% of non-CPR-by-FR-cases; OR 1.57, CI95% 1.06–2.30, p=0.022). Conclusion: Basic-CPR by FR slows down metabolic and respiratory acidosis. This entails better outcomes. These data reinforce universal CPR training programs. References: Shin J, Lim YS, Kim K, Lee HJ, Lee SJ, Jung E, et al . Initial blood pH during cardiopulmonary resuscitation in out-of-hospital cardiac arrest patients: a multicentre observational registry-based study. Critical Care 2017;21:322. Corral E, Casado MI, García-Ochoa MJ, Suárez R. Looking a 'metabolic watch'. The analytical parameters found at the beginning of the resuscitation are predictors of the neurological prognostic in the prehospital cardiac arrest. Resuscitation 2015;96(Suppl 1);148. Conflict of interest: None. Funding: None.